Focal headache during balloon inflation in the vertebral and basilar arteries - Nichols III, Fenwick (1993)
SYNOPSIS Background and Purpose: Headache may be seen in acute cerebrovascular disease. The significance of localized headache in association with vertebrobasilar disease has not been recognized. Summary of Report: We describe a patient with a cerebellar arteriovenous malformation who underwent intravascular balloon occlusion of the vertebral and basilar artery. He developed reproducible patterns of referred pain with balloon inflation at specific sites. Conclusions: Well localized head pain in the setting of acute stroke should alert physicians to the possibility of localized arterial injury. The pattern seen in this patient has been documented in experimental situations, and should be of use in the setting of acute stroke.